Pelatihan dan Pendampingan Pembelajaran Kolaboratif dengan Mengembangakan Bahan Ajar Digital Berbasis Learning Management System (LMS) - Sahronih, Siti; Guntur, Mochamad; Sholeha, Herisa Hardiyanti; Ismuwardani, Zakiyah; Qudwatullathifah, Ratri Nuryani; Bito, Gregorius Sebo; Sariyyah, Nining; Dole, Frumensius B (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2023)
This collaborative learning aims to improve the quality and quantity of cooperation between universities in eastern Indonesia through the implementation of collaborative online learning. Collaborative online learning training involves six educators who will teach.. Based on the results of a survey that has been conducted, it is stated that IPB Cirebon students still use LMS as a lecture system, while Uniflor students have a face-to-face lecture system. Therefore, a collaborative online learning program (PDK) was carried out between IPB Cirebon and Uniflor. The PDK program is implemented using three stages. These stages include starting from initial studies, planning, implementation, monitoring and evaluation. Using stages in the PDK program is the right approach. Active student involvement in every meeting, the development of LMS-based digital teaching materials will be more oriented towards student needs and aspirations. Through active student participation, the PDK program has the potential for better achievements, realizing learning in 2045. Collaborative online learning between two universities can increase digital literacy between students and educators. Collaborative online learning can also develop students' abilities in the 3T area. Through this learning, students can collaborate with other university students.